2016
DOI: 10.1037/bul0000025
|View full text |Cite
|
Sign up to set email alerts
|

Does monitoring goal progress promote goal attainment? A meta-analysis of the experimental evidence.

Abstract: Progress monitoring and goal attainment 2 AbstractControl Theory and other frameworks for understanding self-regulation suggest that monitoring goal progress is a crucial process that intervenes between setting and attaining a goal, and helps to ensure that goals are translated into action. However, the impact of progress monitoring interventions on rates of behavioral performance and goal attainment has yet to be quantified. A systematic literature search identified 138 studies (N = 19,951) that randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
229
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(268 citation statements)
references
References 287 publications
(325 reference statements)
13
229
2
4
Order By: Relevance
“…The relevance of self-regulation techniques for PA behaviour has previously been evidenced (Michie et al, 2009;Samdal et al, 2017;Williams and French, 2011) and systematic reviews have found self-monitoring using pedometers to be effective for increasing PA and improving health outcomes (Bravata et al, 2007;Hobbs et al, 2013). Harkin et al (2016) also found that monitoring goal progress can help promote behaviour change which is in line with a Control Theory framework (Carver and Scheier, 1982) and also Rothman's theory of behavioural maintenance which proposes that outcome satisfaction determines whether behaviour is maintained (Rothman, 2000). Evidence suggests that PA maintenance may be predicted by the realisation of positive social, mental-wellbeing and fitness goals (Brassington et al, 2002;Kassavou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of self-regulation techniques for PA behaviour has previously been evidenced (Michie et al, 2009;Samdal et al, 2017;Williams and French, 2011) and systematic reviews have found self-monitoring using pedometers to be effective for increasing PA and improving health outcomes (Bravata et al, 2007;Hobbs et al, 2013). Harkin et al (2016) also found that monitoring goal progress can help promote behaviour change which is in line with a Control Theory framework (Carver and Scheier, 1982) and also Rothman's theory of behavioural maintenance which proposes that outcome satisfaction determines whether behaviour is maintained (Rothman, 2000). Evidence suggests that PA maintenance may be predicted by the realisation of positive social, mental-wellbeing and fitness goals (Brassington et al, 2002;Kassavou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…if options exist which do not conflict with these). Using a similar point of departure, there are also studies (away from energy) that explore the impact of an individual's mental construction of goal monitoring upon actions that lead towards goal attainment (Harkin et al, 2016). This has all spun out of a research agenda focussing on factors which might make an individual more or less likely to undertake a particular activity (e.g.…”
Section: Energy Feedback Researchmentioning
confidence: 99%
“…The selection was supported by results of study 1 and 2 as well as by evidence of effectiveness. [47]; coping planning (g) [47]; goal setting (behavior) (c) [55]; discrepancy between current behavior and goal (a) [49]; self-monitoring of behavior…”
Section: Phase Ii: Translation Of Research Results Into App Contents mentioning
confidence: 99%